Are Dialysis Units Environmentally Friendly? A Survey Study - Özer, Zülfünaz; Bahçecioğlu Turan, Gülcan; Aksoy, Tülay (Turk Nefroloji Diyaliz ve Transplantasyon Hemsireleri Dernegi, 2021)
Aim: This study was carried out to determine the compliance status of dialysis units in Istanbul with environmental friendly criteria. Material and Method: This cross-sectional and descriptive study was conducted between 5 September 2020 and 20 September 2020. The questionnaire form prepared with the Google Docs program and it was sent online (via e-mail, WhatsApp) to the responsible nurses of 55 dialysis units at the time of the study. Thirty-seven (67%) centers that responded to the questionnaires were included in the study. Results: Of the dialysis units, 70.3% of the wastes are separated electronically, 56.8% of the wastes (plastic, glass, paper) are recycled, 40.5% of them do not use low flow armatures that prevent waste, 54,1% do not use double-stage toilet cisterns, 75.7% do not collect rain water for various uses, 37.8% do not reuse waste water with reverse osmosis, 51.4% do not use motion sensors for lighting, 48,6% of them do not have a hand dryer, 51.4% of them print double-sided, 56.8% take measures to reduce the pressure from printers, 89.2% use both electronic recording system and file and paper. 51.4% of them do not have a bicycle path and bicycle parking area, 67.6% do not encourage the staff to walk or cycle, 59.5% of them give information to their patients about taking care of themselves during extreme heat, 89.2% of them do not use the tele or video conferencing method during the patient training/visits. It was determined that 67.6% of them work to reduce energy consumption, 70.3% of them follow the guidelines that included environmental protection, and 40.5% of them do not make any official efforts to increase environmental sustainability awareness. It was determined that 62.2% of the nurses participating in the study had not heard of the concept of environmentally friendly dialysis/green dialysis. Conclusion: It was determined that there were inadequacy in waste management and problematic fields needing improvement in water management and energy management in dialysis units. It was observed that environmentally friendly practices in dialysis units were insufficient and they were not included in the scope of green dialysis. © 2021, Turk Nefroloji Diyaliz ve Transplantasyon Hemsireleri Dernegi. All rights reserved.
Diyaliz Üniteleri Çevre Dostu mu? Bir Anket Çalışması
Keywords: Conservation of Natural Resources; Dialysis Unit; Environment Friendly; Sustainability